2018
DOI: 10.1093/infdis/jiy013
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Serological Responses in Critically Ill Patients Hospitalized With 2009 Pandemic Influenza A(H1N1) Virus Infection in Canada, 2009–2011

Abstract: Background The kinetics of the antibody response during severe influenza are not well documented. Methods Critically ill patients infected with 2009 pandemic influenza A(H1N1) virus (A[H1N1]pdm09), confirmed by reverse-transcription polymerase chain reaction analysis or seroconversion (defined as a ≥4-fold rise in titers), during 2009–2011 in Canada were prospectively studied. Antibody titers in serially collected sera were determined using hemagglutinin inhibition (HAI) and microneutralization assays. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Although, our results support the assumption that antibody measured in these 262 specimens are representative of levels present prior to infection, this cannot be definitively determined 263 without paired pre-infection specimens. One recent study of antibody kinetics in patients hospitalized 264 found that HAI titers rose rapidly after infection with >80% having HAI titers ≥40 within two weeks [25]; 265 in our study, 89% of patients had specimens collected ≤6 days after illness onset. Similarly, vaccinated 266 subjects had higher HAI and NAI titers against all measured influenza antigens suggesting that these 267 antibodies were produced in response to influenza vaccination.…”
Section: Discussion 223supporting
confidence: 47%
“…Although, our results support the assumption that antibody measured in these 262 specimens are representative of levels present prior to infection, this cannot be definitively determined 263 without paired pre-infection specimens. One recent study of antibody kinetics in patients hospitalized 264 found that HAI titers rose rapidly after infection with >80% having HAI titers ≥40 within two weeks [25]; 265 in our study, 89% of patients had specimens collected ≤6 days after illness onset. Similarly, vaccinated 266 subjects had higher HAI and NAI titers against all measured influenza antigens suggesting that these 267 antibodies were produced in response to influenza vaccination.…”
Section: Discussion 223supporting
confidence: 47%
“…However, this result is consistent with challenge studies finding little antibody response before 7 days post-infection [25]. Another recent study of antibody kinetics in patients hospitalized found that HAI titers rose rapidly after infection with >80% having HAI titers ≥40 within two weeks [26]; in our study, 89% of patients had specimens collected ≤6 days after illness onset. Similarly, vaccinated subjects had higher HAI and NAI titers against all measured influenza antigens suggesting that these antibodies were produced in response to influenza vaccination.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the presence of neutralizing antibodies is considered an important marker of protection against many viruses (23)(24)(25). However, it is also well known that the detection of only neutralizing antibodies can likewise be elusive for many viruses (26). Many anti-HSV vaccine attempts, trials, and projects, with the aim of eliciting neutralizing serum antibodies, such as those using whole virions or full-length viral immunogenic proteins, have been carried out in recent decades without much success in conferring long-lasting reduction of both clinical HSV recurrences and virus shedding rates (5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%